Study of underfill flow in microchip packaging using ansys - Hussin, N.F.R.; Rosli, N. (Penerbit UMP, 2022)
The project was related to microchip application where adhesive fluid is used to stick the microchip onto the electrical flat base. In this project, 5mm of width and length of microchip with 3 different types of solder ball diameter sizes are used in this project. The objective of the project is to study the flow pattern and velocity of fluid during injection based on the decided parameters, which are initial velocity, fluid viscosity, and the diameter of the solder ball. Each parameter that has been set produces a different outcome in terms of flow pattern and velocity of fluid. To maximise the performance of fluid flow in the aspect of uniformity of the fluid flow to fill the gap around the solder ball, the flow pattern and the velocity are being observed and recorded throughout the simulation process.